Caging borders and carceral states: incarcerations, immigration detentions, and resistance - Chase, Robert T. (Justice, power, and politics, 2019)
"This volume considers the interconnection of racial oppression in the U.S. South and West, presenting thirteen case studies that explore the ways in which people have been caged and incarcerated, and what these practices tell us about state building, coercive legal powers, and national sovereignty. As these studies depict the institutional development and state scaffolding of overlapping carceral regimes, they also consider how prisoners and immigrants resisted such oppression and violence by drawing on the transnational politics of human rights and liberation, transcending the isolation of incarceration and the boundaries of domestic law"--